A lay provider delivered behavioral intervention for Syrian refugees and their children in Jordan. (30th September 2020) - Bryant, R; Giardinelli, L; Bawaneh, A; Awwad, M; Hadeel, N; Whitney, C; Akhtar, A
Abstract: Background: Refugees and their children are exposed to many distressing events, including detention in refugee camps. Not surprisingly, refugees are at high risk for common mental disorders. A major barrier to addressing mental health problems in refugees is that most host countries lack sufficient mental health specialists to provide high-intensity treatments. A recent trend has focused on training non-specialists to deliver simple psychosocial programs to those with distress. One such program is Problem Management Plus (PM+) which was developed by the World Health Organization; it comprises 5 small-group sessions that teach behavioural skills to reduce distress. This study reports the first evaluation of group PM+ in a refugee camp. We investigated the extent to which PM+ provided to adult Syrian refugees can benefit their children. Methods: 480 Adult Syrian refugees in the Azraq Refugee Camp were randomized to either PM+ or Treatment as Usual (TAU). Participants were independently assessed prior to the program, immediately following the program, and 3 months later. Outcome variables included anxiety, depression, functioning, posttraumatic stress, and grief and parenting behaviours. Children's psychological wellbeing was assessed in one child of each participant. Results: Of the 650 adult refugees were screened in the camp, 96% met the cut-off for psychological distress and 76% met criteria for functional impairment. 480 participants were randomized to PM+ or TAU. The baseline assessment indicated 85% of refugees met criteria for depression, 84% met criteria for anxiety, and 84% met criteria for posttraumatic stress disorder. The 3-month assessment will be presented following linear mixed modelling to determine the relative gains made by refugees and their children in PM+ and TAU. Conclusions: These findings will be discussed in terms of implementation of scalable programs in refugee settings, and specifically how these can benefit participants and their children.